The Specificity of the Uzbek Shaman Ceremony Folklore - Olim Sadiriddinovich Kayumov (International Journal on Integrated Education, 2022)
In this article, the characteristic features of shamanic ritual folklore, the role of shamanism in the cultural life of the Uzbek people, and its impact on the development of artistic thinking have been determined. Information about shaman sayings and Uzbek shamans, mythological patrons of Uzbek shamans and acceptance of shamanism, factual information about Uzbek shaman rituals are provided. The uniqueness of Uzbek shaman ritual folklore is revealed.